SYMMETRY PROPERTIES AND SOME EXACT SOLUTIONS OF TWO-DIMENSIONAL NONLINEAR EQUATION OF REACTION-CONVECTION-DIFFUSION - Сєров, Микола Іванович; Приставка, Юлія Василівна (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
Li’s symmetry of two-dimensional equation of reaction-convection-diffusion used to build invariant anzatze, reduction and finding its exact solutions.